A Brief Review on Solubility Enhancement Technique: Hydrotropy - Namdev, Bhavesh; Venkatachalam, Senthil; Jawahar, N; Chorsiya, Anushma (Indian Journal of Pharmaceutical Education and Research, 2022)
In this review we have elaborated about number of hypothesis postulated to understand the mechanism of hydrotropic agents, although majority of the postulated hypothesis haven’t justified the solubility enhancement mechanism. Further to it the articles focuses upon the parameters affecting enhancement of solubilizing ability. Hydrotropes are extensively used in drug solubilization, extraction agents for various phytoconstituents, separation agent used for pharmaceutical analysis, as well as for increasing the rate and yield of a chemical reaction due to their unique features. Because of this, hydrotropic solutions possess high industrial demand. While mixed hydrotropy is mostly used in enhancement of solubility, extraction of phytoconstituents and separation by the use of more than one hydrotropic agent. This review article also highlights the applications and future prospects with the employment of hydrotropes and hydrotropic agents in novel drug delivery or parental or oral or tropical systems to enhance solubility profile the drugsare also discussed.
Keywords: Mixed Hydrotropy; Solubilizing agent; Mechanisms of hydrotropes; Application; of Hydrotropes; Solubility; Bioavailability enhancement